2020
DOI: 10.1161/circep.120.008712
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Emerinopathy

Abstract: Background: Mutations in the nuclear envelope genes encoding LMNA and EMD are responsible for Emery-Dreifuss muscular dystrophy. However, LMNA mutations often manifest dilated cardiomyopathy with conduction disturbance without obvious skeletal myopathic complications. On the contrary, the phenotypic spectrums of EMD mutations are less clear. Our aims were to determine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Excessive trabeculation has been observed in several neuromuscular disorders, including specific genetically determined conditions such as Barth syndrome, 69 mitochondrial disorders, 70 nuclear envelopathies, 71 dystrobrevinopathy, 72 myotonic dystrophy, zaspopathy, 73 and myoadenylate deaminase deficiency, 74 as well as Duchenne and Becker types of muscular dystrophy. 75 A causal relationship with the underlying genetic defects, however, has yet to be established, with genotypic-phenotypic heterogeneity largely unexplained.…”
Section: Determinants and Associations Of Excessive Trabeculationmentioning
confidence: 99%
“…Excessive trabeculation has been observed in several neuromuscular disorders, including specific genetically determined conditions such as Barth syndrome, 69 mitochondrial disorders, 70 nuclear envelopathies, 71 dystrobrevinopathy, 72 myotonic dystrophy, zaspopathy, 73 and myoadenylate deaminase deficiency, 74 as well as Duchenne and Becker types of muscular dystrophy. 75 A causal relationship with the underlying genetic defects, however, has yet to be established, with genotypic-phenotypic heterogeneity largely unexplained.…”
Section: Determinants and Associations Of Excessive Trabeculationmentioning
confidence: 99%
“… 19 , 23 In our study, LVSD was observed in just under half of all male EMD variant-carriers, and 13% developed ESHF suggesting that regular monitoring of left ventricular function should be routine. It was also notable that over a quarter of male EMD variant-carriers with cardiac involvement had no reported neuromuscular disease, supporting recent work by Ishikawa et al 24 who suggested the term ‘cardiac emerinopathy’ to describe those patients with an isolated cardiac phenotype.…”
Section: Discussionmentioning
confidence: 53%
“…They are known to bind to the lamina, provide structural integrity, and communicate mechanical cues, thereby participating in signal transduction pathways. Variants of proteins such as emerin, nesprin-1 and 2, lamin A/C, and LAP1 and LAP2 have been reported to be associated with pathological cardiac development and muscular dystrophy [24,29,[42][43][44][45]. The communication of cytoskeleton tension forces is therefore supported by the nuclear envelope proteins, which is particularly important within myocytes.…”
Section: Nuclear Components and Mechanosensingmentioning
confidence: 99%